(untitled) (Pakistan Journal of Science, 2012)
To monitor the effects of various levels of methanolic extract of Peganum harmala (P. harmala) on liver function in broilers birds, 28-days feeding trial involving 240 one-week old broiler chicks was carried out. The birds were grouped into four dietary treatments of -0, 200,250 and 300 mgL-1 of drinking water, which were further replicated 6 times in completely randomized design. Standard management practices were adopted, feed and water were offered ad libitum. At the end of every week, one bird was randomly selected from each replicate, bled to aspirate blood for liver enzymatic activities i.e. Alanine transaminase (ALT), Asparate aminotransferase (AST), Alkaline phosphatase (ALP) and serum protein determination. The liver enzymes i.e. ALT, AST and ALP showed gradual reduction in their concentration under different level of P. harmala methanolic extract. Significantly lower (P<0.05) values for ALT were found for the group Ph-250 except at day-14, where it was significantly low for group Ph-200. The AST levels were significantly (P<0.05) decreased in treated groups as compared to control at all recorded stages. The minimum values were recorded for group Ph-250 at day-14 and 35, while at day-21 and 28 no significant change was observed among the treated groups. The ALP level was significantly (P<0.05) lower in treated groups at all recorded stages. No significant change was observed in serum protein of broiler chicks at any recorded stage. It is concluded that methanolic extract of P. harmala at the dose rate of 250 mgL-1 drinking water may be used to improve serum hepatic parameters in broiler chicks.